CO2 Laser irradiation of GeO2 planar waveguide fabricated by rf-sputtering. Issue 1 (17th February 2015) - Valligatla, S; Chiasera, A; Bazzanella, N; Lunelli, L; Miotello, A; Mazzola, M; Rao, D Narayana; Ferrari, M
Abstract: We present a fabrication protocol combining radio frequency sputtering technique and CO2 laser annealing for GeO2 based planar optical waveguides. The effects of pulsed CO2 laser irradiation on the optical and structural properties of pure GeO2 planar waveguide are evaluated by different techniques as m-line and micro-Raman spectroscopy and AFM measurements. Amorphous GeO2 planar waveguide was fabricated by Radio Frequency magnetron sputtering system on v-SiO2 substrate. An increase of the refractive index of approximately 0.04 at 1.5 μm and a decreasing of the attenuation coefficient from 0.9 to 0.5 dB/cm at 1.5 μm have been observed after pulsed CO2 laser annealing. Raman spectroscopy and AFM results showed that after an adapted pulsed CO2 laser annealing, the resulting materials showed a crystalline environment in which the phase of the crystalline GeO2 varies with varying irradiation time.